Nanoparticles of Dibromo-p-sulfonic Acid-Arsenazo Encapsulated in SBA-15 - Zhai, Qing-Zhou; Hu, Shun; Li, Xiao-Dong; Yu, Hui (Asian Journal of Chemistry, 2011)
DBS-Arsenazo (dibromo-p-sulfonic acid arsenazo, DBS-ASA) nanoparticles were prepared within sileceous SBA-15 mesoporous molecular sieve by liquid method. A series of characterizations including chemical analysis, infrared spectra, powder X-ray diffraction analysis, scanning electron microscopic study, nitrogen adsorption-desorption study, photoluminescence study were used to characterize the host-guest (SBA-15)-(DBS-ASA) nanocomposite compounds. Nitrogen adsorption-desorption study, chemical analysis revealed that DBS-ASA incorporated into the host SBA-15. Nitrogen adsorption measurements revealed mesoporosity for the host-guest nanocomposite materials accompanied by a reduction of the surface area and pore volume, both indications of a decoration of the inner surface of the molecular sieve walls. IR and XRD investigations showed that the mesoporous host structure was still kept in the host-guest composite compounds. XRD measurements proved that the existence of disordered DBS-ASA nanoparticles. SEM investigations showed that the shape of (SBA-15)-(DBS-ASA) was claviform and the size of (SBA-15)-(DBS-ASA) was 328 ± 10 nm. The nonacomposite materials (SBA-15)-(DBSASA) have a property of luminescence at 470 nm and may become a promising luminescent material.